2009
DOI: 10.1345/aph.1l661
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Varenicline in a Veteran Population with a High Prevalence of Mental Illness

Abstract: Cautious treatment initiation and close monitoring of veterans initiated on varenicline are warranted. Furthermore, the results from this study demonstrate the need for prospective effectiveness trials to determine the clinical significance of the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 22 publications
2
27
2
1
Order By: Relevance
“…This rate is consistent with the findings of Purvis et al 29 ; 8% of their study population experienced neuropsychiatric effects ranging from agitation and anxiety to a depressive episode in 1 individual. To date, serious adverse effects such as found in that study and this study have been documented only in case reports and not in other clinical trials.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This rate is consistent with the findings of Purvis et al 29 ; 8% of their study population experienced neuropsychiatric effects ranging from agitation and anxiety to a depressive episode in 1 individual. To date, serious adverse effects such as found in that study and this study have been documented only in case reports and not in other clinical trials.…”
Section: Discussionsupporting
confidence: 93%
“…Unless directly documented by providers upon follow-up, the last dose of medication for each patient was Variable Table 1. (29) Value assumed to occur at the end of a four-week course of treatment. This could skew the data if numerous patients discontinued therapy before completing the full varenicline prescription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…53 It is the first partial agonist of the α4β2 nicotinic acetylcholine receptor to be developed; the dependency effects of nicotine are thought to be mediated at these receptors. 54,55 Varenicline works by stimulating dopamine, which results in reduced cravings and withdrawal symptoms.…”
Section: Vareniclinementioning
confidence: 99%
“…A small number of studies undertaken in populations with mental illness have subsequently been reported but they have been either uncontrolled or underpowered (or both) and therefore unable to properly assess the risk of this condition [32][33][34][35].…”
Section: Vareniclinementioning
confidence: 99%